Análise estereológica de neurônios do corpo amigdaloide e avaliação comportamental de camundongos sob o uso de esteroides anabolizantes - Ribeiro, Melissa Siqueria (2014)
The androgenic-anabolic steroids (AAS) are synthetic derivatives of testosterone abusively used by individuals looking to gain physical strength or aesthetic purposes. Supraphysiological doses of these compounds have been associated with possible damages to nervous tissue, emotional and behavioral adverse effects, such as changes in anxious or aggressive responses. Considering the lack of knowledge about the neural aspects involved in these behavioral changes, and researchs that point to a possible deleterious effect of AAS in the central nervous system (CNS), we investigated the integrity of the number of cell bodies of neurons of the basolateral amygdala (BLA) and the posteroventral medial amygdala nucleus (MePV) of male and female mice. The animals received intraperitoneal injections of testosterone cypionate (Deposteron ®) and stanozolol (Winstrol Depot ®) supraphysiological doses, twice a week in the period of 33 days. As a control group received 0.9% sterile saline solution on the same days. For quantification and behavioral tests, analyses on the number of cell bodies of neurons was performed. The treated mice showed an increase in anxiety-related behaviors in the elevated plus maze test, and no changes were observed in the general motor activity in the open field and parameters of aggressiveness in the resident-intruder test model. The two AAS were able to significantly reduce the number of neuronal cell bodies in both analyzed areas, suggesting a process of neuronal death due to apoptosis induced by the AAS.